2014
DOI: 10.1002/pon.3721
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer survivors' beliefs about screening and treatment decision-making experiences in an era of controversy

Abstract: Objective Controversy about the costs and benefits of screening and treatment of prostate cancer (PCa) has recently intensified. However, the impact of the debate on PCa patients has not been systematically studied. Methods We assessed knowledge of, and attitudes toward, the U.S. Preventive Services Task Force’s (USPSTF) May 2012 recommendation against PSA-based screening among men diagnosed with clinically localized PCa, and tested whether exposure to the recommendation and associated controversy about over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…International guidelines suggest PCa screening by prostate‐specific antigen (PSA) and digital rectal examination (DRE) in all RTR male over 50 years of age with life expectancy of at least 10 years . Given that screening is nowadays controversial in the general population, it should also be questioned for RTR . Furthermore, PCa incidence is expected to increase in RTR: through the improved medical cares of RTR in the last decades, inducing a longer life expectancy and graft survival, and through the bias of screening, urologists will inevitably have to manage more RTR with PCa.…”
Section: Introductionmentioning
confidence: 99%
“…International guidelines suggest PCa screening by prostate‐specific antigen (PSA) and digital rectal examination (DRE) in all RTR male over 50 years of age with life expectancy of at least 10 years . Given that screening is nowadays controversial in the general population, it should also be questioned for RTR . Furthermore, PCa incidence is expected to increase in RTR: through the improved medical cares of RTR in the last decades, inducing a longer life expectancy and graft survival, and through the bias of screening, urologists will inevitably have to manage more RTR with PCa.…”
Section: Introductionmentioning
confidence: 99%
“…[77–80] Two survey studies showed that there was awareness on the screening controversy yet the majority of men still believed that screening saved lives and should be used despite the USPSTF recommendation. [81, 82] Jemal et al examined the recent changes in stage specific incidence and PSA testing rates. The authors used SEER data on invasive PC incidence data from 2005 to 2012 and had the availability of 2013 incidence data from one registry (Georgia).…”
Section: Methodsmentioning
confidence: 99%
“…To qualify as informed decision making, people must be aware of their cancer risk and discuss the benefits and possible harms of screening with their health care provider ( 4 ). Despite the emphasis on the value of informed decision making in guidelines issued by the US Preventive Services Task Force (USPSTF) and other organizations, studies show that few people with average risk for cancer are aware of the ongoing debate about the potential harms associated with some types of cancer screening and may overestimate benefits and underestimate potential risks ( 5 7 ). Some studies show that interventions at clinics, with decision aids such as questionnaires and counseling, can increase patient understanding of potential harms of screening and may facilitate discussion between patients and their health care providers ( 7 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the emphasis on the value of informed decision making in guidelines issued by the US Preventive Services Task Force (USPSTF) and other organizations, studies show that few people with average risk for cancer are aware of the ongoing debate about the potential harms associated with some types of cancer screening and may overestimate benefits and underestimate potential risks ( 5 7 ). Some studies show that interventions at clinics, with decision aids such as questionnaires and counseling, can increase patient understanding of potential harms of screening and may facilitate discussion between patients and their health care providers ( 7 11 ). However, little is known about how people at average risk acquire screening-related information and if and how they use this information in discussions with their providers to arrive at a screening decision.…”
Section: Introductionmentioning
confidence: 99%